Practical synthesis of isocoumarins via Rh(III)-catalyzed C–H activation/annulation cascade - Gao, Qian-Ci; Li, Yi-Fei; Xuan, Jun; Hu, Xiao-Qiang (Beilstein Journal of Organic Chemistry, 2023)
Herein, we report an unprecedented Rh(III)-catalyzed C–H activation/annulation cascade of readily available enaminones with iodonium ylides towards the convenient synthesis of isocoumarins. This coupling system proceeds in useful chemical yields (up to 93%) via a cascade C–H activation, Rh-carbenoid migratory insertion and acid-promoted intramolecular annulation. The success of gram-scale reaction and diverse functionalization of isocoumarins demonstrated the synthetic utility of this protocol.
Keywords: C–H activation; enaminone; iodonium ylide; isocoumarin; rhodium catalysis

(untitled) - Barry, R. D. (Chem. Rev., 1964)

(untitled) - Tianpanich, K.; Prachya, S.; Wiyakrutta, S.; Mahidol, C.; Ruchirawat, S.; Kittakoop, P. (J. Nat. Prod., 2011)

(untitled) - Chaudhary, N. K.; Pitt, J. I.; Lacey, E.; Crombie, A.; Vuong, D.; Piggott, A. M.; Karuso, P. (J. Nat. Prod., 2018)

(untitled) - Bai, M.; Zheng, C.-J.; Huang, G.-L.; Mei, R.-Q.; Wang, B.; Luo, Y.-P.; Zheng, C.; Niu, Z.-G.; Chen, G.-Y. (J. Nat. Prod., 2019)

(untitled) - Cai, R.; Wu, Y.; Chen, S.; Cui, H.; Liu, Z.; Li, C.; She, Z. (J. Nat. Prod., 2018)

(untitled) - Yao, T.; Larock, R. C. (J. Org. Chem., 2003)

(untitled) - Mallampudi, N. A.; Reddy, G. S.; Maity, S.; Mohapatra, D. K. (Org. Lett., 2017)

(untitled) - Chen, B.; Ma, S. (Org. Lett., 2013)

(untitled) - Faizi, D. J.; Issaian, A.; Davis, A. J.; Blum, S. A. (J. Am. Chem. Soc., 2016)

(untitled) - Xing, L.; Zhang, Y.; Li, B.; Du, Y. (Org. Lett., 2019)

(untitled) - Finney, L. C.; Mitchell, L. J.; Moody, C. J. (Green Chem., 2018)

(untitled) - Xia, Q.; Wang, Q.; Yan, C.; Dong, J.; Song, H.; Li, L.; Liu, Y.; Wang, Q.; Liu, X.; Song, H. (Chem. – Eur. J., 2017)

(untitled) - Bera, S.; Mondal, P.; Sarkar, D.; Pathi, V. B.; Pakrashy, S.; Datta, A.; Banerji, B. (J. Org. Chem., 2021)

(untitled) - Pati, B. V.; Banjare, S. K.; Das Adhikari, G. K.; Nanda, T.; Ravikumar, P. C. (Org. Lett., 2022)

(untitled) - Li, Y.; Wang, Q.; Yang, X.; Xie, F.; Li, X. (Org. Lett., 2017)

(untitled) - Subramanian, V.; Batchu, V. R.; Barange, D.; Pal, M. (J. Org. Chem., 2005)

(untitled) - Luo, F. (Chin. J. Org. Chem., 2019)

(untitled) - Pichette Drapeau, M.; Gooßen, L. J. (Chem. – Eur. J., 2016)

(untitled) - Miura, M.; Tsuda, T.; Satoh, T.; Pivsa-Art, S.; Nomura, M. (J. Org. Chem., 1998)

(untitled) - Nandi, D.; Ghosh, D.; Chen, S.-J.; Kuo, B.-C.; Wang, N. M.; Lee, H. M. (J. Org. Chem., 2013)

(untitled) - Warratz, S.; Kornhaaß, C.; Cajaraville, A.; Niepötter, B.; Stalke, D.; Ackermann, L. (Angew. Chem., Int. Ed., 2015)

(untitled) - Hong, C.; Yu, S.; Liu, Z.; Zhang, Y. (Org. Lett., 2022)

(untitled) - Jiang, G.; Li, J.; Zhu, C.; Wu, W.; Jiang, H. (Org. Lett., 2017)

(untitled) - Chinnagolla, R. K.; Jeganmohan, M. (Chem. Commun., 2012)

(untitled) - Chen, X. Y.; Zhang, X.; Wan, J.-P. (Org. Biomol. Chem., 2022)

(untitled) - Zhou, S.; Wang, J.; Wang, L.; Song, C.; Chen, K.; Zhu, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Wu, W.; Wu, X.; Fan, S.; Zhu, J. (Org. Lett., 2022)

(untitled) - Zhou, S.; Yan, B.-W.; Fan, S.-X.; Tian, J.-S.; Loh, T.-P. (Org. Lett., 2018)

(untitled) - Zhao, Y.-R.; Li, L.; Xu, G.-Y.; Xuan, J. (Adv. Synth. Catal., 2022)

(untitled) - Jiang, Y.; Li, P.; Zhao, J.; Liu, B.; Li, X. (Org. Lett., 2020)

(untitled) - Li, R.; Hou, Y.-X.; Xu, J.-H.; Gao, Y.; Hu, X.-Q. (Org. Chem. Front., 2022)

(untitled) - Yang, Z.; Liu, C.; Lei, J.; Zhou, Y.; Gao, X.; Li, Y. (Chem. Commun., 2022)

(untitled) - Hu, X.-Q.; Liu, Z.-K.; Hou, Y.-X.; Zhang, G.; Gao, Y. (Chem. Commun., 2021)

(untitled) - Hu, X.-Q.; Liu, Z.-K.; Hou, Y.-X.; Xu, J.-H.; Gao, Y. (Org. Lett., 2021)

(untitled) - Gao, Y.; Nie, J.; Li, Y.; Li, X.; Chen, Q.; Huo, Y.; Hu, X.-Q. (Org. Lett., 2020)

(untitled) - Xia, Y.; Wang, J. (Chem. Soc. Rev., 2017)

(untitled) - Chen, J.-R.; Hu, X.-Q.; Lu, L.-Q.; Xiao, W.-J. (Chem. Soc. Rev., 2016)

(untitled) - Cai, B.; Xuan, J. (Chin. J. Org. Chem., 2021)

(untitled) - Kumar, S.; Nunewar, S.; Kanchupalli, V. (Asian J. Org. Chem., 2022)